MARIA CANTACUZINO, O PRINȚESĂ A CULTURII - MOȚOC, Radu (BIBLIOPOLIS, 2020)
The article is an evocation of the personality of Maria Cantacuzino, representative of the Romanian noble dinasty. She was a entertainer of a cultural life in Yassy. In 1850 she is established in France for medical treatment. In Paris, M. Cantacuzino became very popular in the intelectual and artistic circles. Some French painters made her portrait; she served as a model for an sculptural portrait.